Penegakan Kepastian Hukum Dalam Unsur Tindak Pidana Penganiayaan Berencana Pada Putusan Pengadilan Negeri MARISA 72/PID.B/2019/PN.MAR - Arif Al Jibran, Farel; Adhari, Ade (UNES Law Review, 2024)
Enforcing legal certainty in criminal acts of serious abuse is an important aspect of a just justice system. This study analyzes the application of the elements "whoever" and "commits serious maltreatment" in the crime of serious maltreatment and their relevance to legal certainty in law enforcement. Clear provisions regarding actions that are considered serious abuse and who is responsible for these actions are the main key. With this clarity, justice can be better served because all parties are subject to the same laws. Apart from that, applying appropriate punishment is also a means of providing justice to victims and society as a whole. The research results show that the application of these two elements is in accordance with the principles of justice and legal certainty. Thus, legal certainty in enforcing criminal acts of serious ill-treatment is an important basis for creating a just and civilized society. Through normative juridical analysis research methods, and supported by the fact that clarity in the law provides certainty for society and upholds justice. So enforcing legal certainty in criminal acts of serious abuse is a crucial step in maintaining justice and public order. By understanding and applying the principles of legal certainty, the justice system can function effectively to protect individual rights and provide justice to all parties involved.